Nonsyndromic Multiple Supplemental Teeth in Mandibular Premolar Regions: A Rare Case Report - Parinitha, MS (Journal of Orofacial Research, 2013)
Supernumerary teeth are extra teeth above the normal number. Erupted supernumerary teeth in premolar region are rarer than in incisor and molar region. This paper reports a rare case of bilaterally erupted supernumerary (supplemental, where the supernumerary resembles the tooth of the normal series) teeth in mandibular arch of permanent dentition and discusses the etiology and clinical significance of this condition.